The Resistance of Soybean Genotypes to The Pod Feeding Insects - Krisnawati, Ayda; Adie, Mochammad Muchlish (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2019)
One of the constraints impeding soybean production in the tropics is yield losses due to the damage by pod feeding insects. The research objective was to identify the resistance of soybean genotypes to the pod feeders. The existence of the pod feeding insects was evaluated on 24 soybean genotypes planted in Ngawi (Indonesia) in 2016. The experiment was arranged in a randomized block design with two environmental conditions. The first environmental condition was plants controlled by insecticide during plant growth, and the second condition was plants controlled by insecticide only up to 45 days after planting (dap). The pod feeding insects included pod sucking bug (Riptortus linearis), pod borer (Etiella zinckenella), and podworm (Helicoverpa sp.). The damage intensity of pod sucking bug at 45 dap of controlled environment reached 60.24%, meanwhile the damage intensity of pod borer and podworm were 46.08% and 3.85%, respectively. This indicates that the natural population of pod sucking bug is relatively high and dominant. Of 24 soybean genotypes tested, NSP-16-2-8 was consistently resistant on environments with and without insecticide application, whereas NSP-16-1-4 was consistently resistant to the pod borer attack. Those genotypes were potential to be used as source of genes for pod feeding insects’ resistance in the breeding program.